2013
DOI: 10.2527/jas.2012-6079
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of concentrations of iron and other minerals in longissimus muscle of Angus cattle1

Abstract: The objective of this study was to characterize variation and identify SNP and chromosomal regions associated with mineral concentrations in LM of Angus beef cattle. Samples of LM from 2,285 Angus cattle were obtained, and concentrations of 7 minerals, including iron, magnesium, manganese, phosphorus, potassium, sodium, and zinc, were quantified. Genomic DNA extracted from the ground beef sample used for mineral composition was genotyped with the Bovine SNP50 Infinium II BeadChip, and effects of SNP on each tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 31 publications
1
24
2
Order By: Relevance
“…Mateescu et al (2013a) estimated the heritability based on pedigree information and phenotypic data to be 0.48, 0.00, and 0.15 for LTL iron, potassium, and sodium, respectively. The proportions of phenotypic variation explained by the BovineSNP50 assay were 0.37, 0.03, and 0.09 for iron, potassium and sodium, respectively (Mateescu et al, 2013b). These results are in general agreement with the findings of the current study for the traits of iron and sodium.…”
Section: Longissimus Thoracis Et Lumborum (Ltl) B M Semitendinossupporting
confidence: 82%
See 2 more Smart Citations
“…Mateescu et al (2013a) estimated the heritability based on pedigree information and phenotypic data to be 0.48, 0.00, and 0.15 for LTL iron, potassium, and sodium, respectively. The proportions of phenotypic variation explained by the BovineSNP50 assay were 0.37, 0.03, and 0.09 for iron, potassium and sodium, respectively (Mateescu et al, 2013b). These results are in general agreement with the findings of the current study for the traits of iron and sodium.…”
Section: Longissimus Thoracis Et Lumborum (Ltl) B M Semitendinossupporting
confidence: 82%
“…This is supported by Wiener et al (2009) who showed a significant effect of the myostatin mutation in South Devon cattle for both PUFA and MUFA concentrations. Outside of the myostatin mutation, Mateescu et al (2013b) reported 16 SNP in a single Mb region (103-104 Mb) on BTA2 to explain 1.33% of the phenotypic variation of iron content, although the region reported by Mateescu et al (2013b) does not overlap with the regions reported in the current study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The estimates of additive genetic and residual variance from the BayesC analyses were then used to run the BayesB analyses [18] to estimate SNP effects. The parameter π was set to 0.9995 such that the number of SNP effects to be estimated was less than the number of animals with data (449 364 × (1 - π) = 224 SNPs), as suggested by Mateescu et al [9]. The BayesB analysis fits separate variances for each SNP in the model, which allows large-effect SNPs to be estimated without excessively regressing their effects towards 0.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it has been shown that mineral content in tissues is in part genetically determined and heritable [8,9] and that the genes involved may act via receptor, transporter and chaperone proteins [1]. …”
Section: Introductionmentioning
confidence: 99%